Adsorption of Lead(II) Ions using Coconut Fiber’s (Cocos nusifera L.) Activated by Sodium Hydroxide - Gatut A. Wardani; Dea D. Pamungkas; Winda T. Wulandari; Fajar Setiawan; Estin Nofiyanti (Universitas Tadulako, 2020)
The use of green coconut fiber waste to adsorb lead(II) ions has been successfully carried out. Coconut fiber was activated first using sodium hydroxide before being used as an adsorbent. The optimum time needed for green coconut fiber to adsorb lead(II) ions was 30 minutes with the percentage of ions adsorbed by 94.34%. The lead(II) adsorption kinetics on green coconut fiber model with R2 value of 0.999 and k value of 38.95 x 10-4 minutes-1. Adsorption isotherm from lead(II) on coconut fiber followed the Langmuir adsorption model with R2 value of 0.984 and adsorption capacity of 0.070 g.mg-1.